ACETYLSALICYLIC ACID: WHAT'S NEW IN THE OLD DRUG? - I. V. Zhirov (Столичная издательская компания, 2015)
The results of recent trials on acetylsalicylic acid (ASA) efficacy are presented. Data potentially related to the possibility of ASA indications extension is discussed, in particular that referring to the cancer prevention. This ASA indication should be confirmed in additional studies.